Traditional Chinese Medicine Can Improve Liver Microcirculation and Reduce Portal Hypertension in Liver Cirrhosis - Lieming, Xu; Jie, Gu; Xiong, Lu; Yang, Zhou; Tian, Tian; Jie, Zhang; Hong, Xu (IntechOpen, 2012)
None